Prehistoric predators - Black, Riley (Kennebunkport, Maine Applesauce Press, 2015)
The biggest baddies of the prehistoric world -- the carnivores -- come alive in Prehistoric Predators. From favorites like T-Rex and Giganotosaurus, to the ferocious Spinosaurus and terrifying Megalodon, the stunning full-color illustrations from renowned paleoartist Julius Csotonyi make these dangerous creatures spring to life on each page. Bursting with fascinating facts written by National Geographic contributor Brian Switek, dynamic artwork, and a unique dino-skin textured cover, this is the perfect book for dinosaur lovers of every age!
Includes index
Ages 8-12